Alcohol use after metabolic and bariatric surgery: a qualitative investigation of the relation with mood and food - Lisa R. Miller-Matero; Alyssa Vanderziel; Erin N. Haley; Kristina M. Jackson; Roland S. Moore; Aaron Hamann; Arthur M. Carlin; Jeffrey Genaw; Jordan M. Braciszewski (Health Psychology and Behavioral Medicine)
Background: Individuals who undergo metabolic and bariatric surgery are at increased risk for an alcohol use disorder. Clarity on the relationships between mood, food, and alcohol use could inform interventions to reduce alcohol use and mitigate risk of alcohol use disorders after metabolic and bariatric surgery (MBS).Methods: Twenty patients who underwent MBS at a single health care system and reported engaging in post-operative alcohol use were recruited. Participants were between 6 months and 3 years post-operative and reported consuming alcohol at least 2–3 times per month. Participants engaged in a 1-hour semi-structured interview about factors influencing post-operative mood, eating behaviors, and alcohol use. All interviews were recorded, transcribed, and coded by two independent raters.Results: Statements by participants were deductively coded within different themes: (1) changes in mood, (2) changes in eating patterns, and (3) unintended alcohol use and eating. Participants reported positive changes in mood and eating behaviors following MBS, but also indicated potential for negative mood states and new eating patterns. They also suggested that mood was a driver of both eating and alcohol use, including unintended (i.e. unplanned) eating and unintended alcohol use. However, most did not consume food and alcohol at the same time.Discussion: Food and alcohol may be used as a coping strategy for mood, though they are not often consumed together. There is currently a lack of post-operative interventions to reduce alcohol use and findings suggest that interventions could simultaneously target mood, unintended eating, and alcohol use.